(untitled) (Fiep Bulletin - online, 2016)
Before the description of what is, or better, of what could be physical education (PE) in Europe at the beginning of the 21. century, in a so-called idealistic model based however on the official texts of the French and German speaking European countries, the author gives a short analyse of the evolution of the concept of ?Physical Education‘.After a rough outline of the aims, the contents and the methodological procedures of contemporary PE follows a brief look upon the concrete situation as well as on some major problems to which this European P.E. is actually confronted.